The Ethics of Investing: A Reply to William Irvine - Larmer, Robert (Journal of business ethics, 1997)
In a recent article in this journal entitled "The Ethics of Investing", William Irvine argues that what he calls the 'Evil-Company Principle' is an inadequate guide to ethical investing. In its place, he proposes what he calls the 'Enablement Principle'. In reply, I argue that his rejection of the Evil-Company Principle is premature and that his Enablement Principle presupposes acceptance of the Evil-Company Principle.